Discovery of a Tat HIV-1 inhibitor through computer-aided drug design. Issue 4 (2003) - Esquieu Esquieu, Didier Didier; Péloponèse Péloponèse, Jean-Marie Jean-Marie; Opi Opi, Sandrine Sandrine; Gregoire Gregoire, Catherine Catherine; de Mareuil de Mareuil, Jean Jean; Watkins Watkins, Jennifer Jennifer; Campbell Campbell, Grant Grant; Dunot Dunot, Jean-Pierre Jean-Pierre; Sturgis Sturgis, James James; Witvrouw Witvrouw, Myriam Myriam; Pannecouque Pannecouque, Christophe Christophe; de Clercq de Clercq, Erik Erik; et al.
Abstract : Tat is a regulatory HIV-1 protein, which has the particularity to be secreted very early by HIV-infected cells. The extra cellular roles of Tat are suspected to be the main cause of the maintenance of reservoirs of HIV-infected cells and the failure of actual AIDS therapies to eradicate HIV. This study describes the rationale used to design molecules that bind to a target area containing an hydrophobic pocket identified in the 2D-NMR structure of Tat. Molecules were synthesized and the derivative named TDS2 was shown to be a Tat inhibitor. Fluorescence revealed that TDS2 binds in the target area, which is conserved across five different Tat variants representative of the main HIV-1 subtypes. TDS2 inhibited in vitro HIV-1 replication in human T-cells. Further chemical modifications remain necessary to enhance affinity to Tat and reduce cytotoxicity.